Penerapan Data Mining Untuk Menentukan Jenis Asuransi Yang Paling Diminati Di PT AIA Financial Dengan Metode Clustering - Fahrul Razi; Vany Terisia; Diana Yusuf (ITB Ahmad Dahlan Jakarta, 2023)
Finding information that is concealed in databases is referred to as data mining. Data mining is a process used to extract and find relevant information and related knowledge from numerous very big datasets using statistical, mathematical, artificial intelligence, and machine learning approaches. The steps involved in the data mining process start with the selection of data from the source data to the target data, followed by preprocessing to enhance the quality of the data, transformation, data mining, and stages of interpretation and assessment that result in new information. Organizing data sets into many groups through the process of clustering ensures that objects in one group share a lot in common and differ greatly from those in other groups. Data mining technique K-Means Clustering divides data into one or more clusters. RapidMiner is the program used in this data mining application, which uses the Knowledge Discovery in Databases (KDD) stage. According to this report, AIA Family First Protection, AIA Prolink, and AIA Life Secure are the three most popular insurance products. With the use of this research, PT. AIA Financial will be able to identify the most popular insurance product categories and market these products to the general public.